What Configurational Conditions Promote the Integration of Culture and Tourism? A Fuzzy-Set Qualitative Comparative Analysis Based on China’s Provincial Data - Yunyun Tang; Kaigang Yi; Zijian He; Fan Zhang (SAGE Open)
Although the integration of culture and tourism led to an increasing interest among scholars, there has been insufficient attention to the scientific evaluation of its quality, and the complex influencing mechanisms at the macrogeographic level remain unclear. To address these issues, this study assesses the integration level of culture and tourism using the entropy weight TOPSIS method based on a newly constructed evaluation index system, and subsequently summarizes its configuration patterns based on the fuzzy-set qualitative comparative analysis method. We identified four high-level integration models emphasizing the critical role of technological innovation and regional economy, namely the technology-led environment supporting model, technology-led multi-synergy model, economy-technology-led talent supporting model, and economy-technology-led comprehensive driving model. We also found five paths leading to low-level integration, which showed a casual asymmetry relationship. Our research can provide policymakers with important guidelines on how to promote the integration of culture and tourism.